2019
DOI: 10.1038/s41598-019-53184-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cross-species transmission of hemoplasmas at the wild-domestic felid interface in Chile using genetic and landscape variables analysis

Abstract: The co-occurrence of domestic cats (Felis silvestris catus) and wild felids in rural landscapes can facilitate pathogen transmission. However, in the relatively-isolated regions of southern South America there have been no comprehensive studies to assess disease transmission risks between domestic cats and forest-dwelling wild felids such as guigna (Leopardus guigna). We evaluated hemoplasma infection and the possibility of transmission between domestic cats and guignas by comparing spatial and phylogenetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 69 publications
5
37
1
Order By: Relevance
“…Likewise, M. haemofelis was previously identified in one Darwin fox (Lycalopex fulvipes) from Chiloe (Cabello et al, 2013), and in kodkods (Leopardus guigna) (9.8% [10/102]) from southern Chile (Sacristán et al, 2019). As described before in mustelids, haemotropic Mycoplasma spp.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Likewise, M. haemofelis was previously identified in one Darwin fox (Lycalopex fulvipes) from Chiloe (Cabello et al, 2013), and in kodkods (Leopardus guigna) (9.8% [10/102]) from southern Chile (Sacristán et al, 2019). As described before in mustelids, haemotropic Mycoplasma spp.…”
Section: Discussionsupporting
confidence: 59%
“…It is suggested that the haemoplasma transmission network can involve kodkod and Darwin foxes (Sacristán et al, 2019).…”
Section: Interaction Between Minks and Domestic Dogs Was Reported Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies supported the fact that hemotrophic mycoplasmas have evolved along with a broad diversity of mammal species [ 3 , 70 ]. Chile is not an exception, since hemoplasmas have already been reported in dogs, cats, South American camelids, and wild animals (foxes, kodkod, and bats) [ 43 , 45 , 46 , 47 , 48 , 49 , 71 , 72 ]. To our knowledge, this is the first report of hemotrophic mycoplasmas in rodents from Chile.…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, hemoplasmas have been reported in dogs [ 41 , 42 , 43 ], cats [ 43 , 44 , 45 , 46 ], camelids [ 47 ], and associated fleas [ 45 ]. In wild animals, even though hemoplasmas were detected in Darwin’s foxes ( Lycalopex fulvipes ) [ 48 ], bats ( Histiotus macrotus , Histiotus montanus and Myotis chiloensis ) [ 49 ], and kodkods ( Leopardus guigna ) [ 46 ], there are no studies on rodents from Chile so far.…”
Section: Introductionmentioning
confidence: 99%